Um corpo como fronteira: parentesco e identificações entre descendentes nipônicos "mestiços" - Hatugai, Érica Rosa (2018)
This research analyses the figure of the “mixed-race” person, the ‘mixed’ family comprised of Japanese descendants, and non-descendants, most of whom live in the city of Marília, a countryside city at 446 kilometers away from São Paulo, Brazil. The data show a notion of fluid Japaneseness of the “mixed-race” person, who is thus intertwined with the concepts of corporality, modes, and tensions characteristic of a “Japanese” relationship. About the identification of the “mixed-race” person and ‘mixed’ families, the research shows that the way they perceive themselves and the way they are represented lead to clashes and tensions upon the notions of culture and “Japanese” relationship when compared to families only comprised of Nikkei members. This research approaches the place of the person of “mixed-race” and the ‘mixed’ family in the history of Japanese immigration to Brazil, raising the role of alliances and conflicts present in the notion of “Japanese” relationship. The absence of such a theme in the scientific literature of the Japanese immigration to Brazil may have obfuscated its debate up to the present, in despite of the objective reality and social tensions still alive in this phenomenon. Therefore, this research aims at presenting new elements to help reflect upon one of the many repercussions of the Japanese immigration and presence in Brazil.